Penyelenggaraan Perlindungan Anak Sebagai Korban Kekerasan Seksual (Studi di UPTD PPA Kabupaten Banyumas) - Muhammad, Imam Maulana; Susanti, Rahtami (Fakultas Hukum Universitas Islam Batik Surakarta, 2024)
Sexual violence against children is a criminal offense aimed at children as victims and has a major influence on children such as on the physical, psychological, and social well-being of children. Cases of sexual violence revealed in Banyumas Regency in the 2021-2023 timeframe are still experiencing ups and downs. This is certainly a concern for the Banyumas Regency government to form a Banyumas Regency Regional Regulation and Regent Regulation as mandated by the Child Protection Law. The Technical Implementation Unit for the Protection of Women and Children was established by the local government to provide services for women and children who experience violence, discrimination and protection, prevention and handling of child abuse cases. The purpose of this study is to analyze the implementation of child protection as a victim of sexual violence and analyze the inhibiting factors of the Technical Implementation Unit for the Protection of Women and Children in Banyumas Regency in carrying out its duties. This research uses normative and empirical juridical methods, the subject of this research is UPTD PPA Banyumas Regency. The data collection techniques used in this research are observation, interviews, literature study and documentation. While the data analysis technique uses a qualitative descriptive analysis method, namely all the data that has been obtained is then explained in detail and systematically in the form of written words. The results of this study concluded that in the process of handling cases, UPTD PPA Banyumas Regency carried out its duties and functions in accordance with its role. The inhibiting factors in handling victims include law, law enforcement, facilities, society and culture. Keywords: Implementation, Child Protection, Sexual Violence